Neurodevelopmetal effects of maternal blood pressure management with noradrenaline during general anaesthesia for nonobstetric surgery in the pregnant rabbit model. Issue 6 (9th June 2022) - Bleeser, Tom; Van Der Veeken, Lennart; Basurto, David; Valenzuela, Ignacio; Brenders, Arjen; Van Hoof, Lucas; Emam, Doaa; Vergote, Simen; Van de Velde, Marc; Devroe, Sarah; Deprest, Jan; Rex, Steffen
Abstract : BACKGROUND: In pregnant women, anaesthesia-induced hypotension is commonly treated using phenylephrine or noradrenaline, the rationale being to maintain uterine perfusion pressure and thereby uterine blood flow. Evidence for this strategy during general anaesthesia for nonobstetric surgery is absent. OBJECTIVE: To analyse the effects of treating anaesthesia-induced hypotension with noradrenaline on brain development of rabbit foetuses of mothers subjected to general anaesthesia for nonobstetric surgery. We hypothesised that treatment of maternal hypotension would improve foetal outcomes. DESIGN: Randomised controlled laboratory study using 21 pregnant rabbits (does) at 28 days of gestation. INTERVENTION: Two hours of sevoflurane anaesthesia for a laparotomy without treatment of anaesthesia-induced hypotension (hypotension group) or with maintaining maternal mean arterial pressure above 80% of the awake value using noradrenaline (noradrenaline group). In the control group, does remained untouched. At term, all pups were delivered by caesarean section. One day later, the neurobehaviour of the pups was assessed and brains were harvested. MAIN OUTCOMES: Neuron density in the frontal cortex for the comparison of noradrenaline groups versus hypotension groups was the primary outcome; the neurobehavioural scores and other histological outcomes were secondary outcomes. RESULTS: In the noradrenaline groups and hypotension groups, neuron density in the frontal cortex was similar (1181 ± 162 versus 1189 ± 200 neurons mm −2, P = 0.870). However, significantly less foetal survival, lower sensory scores in neurobehavioural assessment and less proliferation were observed in the noradrenaline group when compared with the hypotension group. Neuron densities in other regions, total cell densities, biometrics and synaptogenesis were not affected. There were no differences between the control group and hypotension group. CONCLUSION: During general anaesthesia for nonobstetric surgery in rabbits, treatment of anaesthesia-induced hypotension using noradrenaline did not affect neuron densities but was associated with impaired foetal outcomes according to several secondary outcome parameters. Further studies are needed to investigate any clinical relevance and to determine the target blood pressure in pregnant women during general anaesthesia.